Communication and Delivery of Project Activities: A Case Study of Selected Organisations in Kabale Municipality - AINE, ONAN (Kabale University, 2022)
A Dissertation Submited to the Faculty of Post Graduate Studies in Partial Fulfilment of the Requirements for the Award of Master’s in Project Planning and Management of Kabale University